Antibacterial potential of Enterococcus faecium strains isolated from ewes' milk and cheese - Rivas, Franco Paolo (2012)
The study was conducted to evaluate the antibacterial activity of three bacteriocin-producing Enterococcus faecium strains (TW15, TW20 and TW22) isolated from ewes' milk and cheese sampled in the Patagonian region of Argentina. The strains were tested against spoilage and pathogens microorganisms showing antimicrobial activity towards 4 strains of Listeria monocytogenes, one strain of Listeria innocua and 2 strainsof Staphylococcus aureus. E.faecium TW15, E.faecium TW20 and E.faecium TW22 were sensitive to vancomycin. Furthermore, investigation of virulence factors revealed the absence of the genes encoding them. The bacteriocin-like substances (BLISs) produced by the 3 strains were thermostable, pH resistant and canbe expressed even in the presence of NaCl (3.0. g/100. g). Moreover, they prove to have a bactericidal mode of action. Results from physicochemical and biochemical characteristics of BLIS produced by these. E.faecium strains make them potential candidates to aid in preservation of foods.